Register dalam Interaksi Waria di Kabupaten Lombok Timur - Fitriyah, Melisa; Kurniawan, Muh. Ardian (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study aimed to describe the transgender language registers in East Lombok regency, in accordance with the problems: (a) the form of the language registers used by  ransgender, (b) the meaning of the transgender language register, (c) the function of the use of the transgender language register. This type of research uses descriptive qualitative research. Techniques of data collection is done by tapping technique, consider involve ably, and record. While the data analysis technique is done by reviewing data, classifying data, analysis and drawing conclusions. Data validity is obtained by triangulation of data. Based on the results of the analysis of the registers in the interaction of transgender language in East Lombok regency, can be drawn conclusion that is: first, the form of transgender language registers can be classified into two that is besed on source and relationship. Second, the meaning of the transgender language registers include between words interpreted with meaningful words. The word is interpreted as a word used to express the intention, while the word meaning is the word that became the intent. as in the word "Dendong><Dandan" word grooming and dangled with the word dendong and dendong word meaning word grooming. Third, the function of the use of transgender language registers are self and group identity, attitude change, pride and confidence.Keywords: form, meaning, and function, transgender language register.